A hybrid halobismuthate light-harvesting material with an optical band gap of 1.70 eV. (26th October 2016) - Kotov, Vitalii Yu.; Ilyukhin, Andrey B.; Birin, Kirill P.; Laurinavichyute, Veronika K.; Sadovnikov, Alexey A.; Dobrokhotova, Zhanna V.; Kozyukhin, Sergey A.
Abstract : The product of Br–I substitution in 1-D (C15 H14 N4 )BiBr5 ·H2 O can be proposed as a promising material for solid-state solar cells. Abstract : A new organic–inorganic hybrid material (C15 H14 N4 )BiBr5 ·H2 O with an optical band gap of 2.24 eV, having 1-D chains of bromobismuthate anions in its composition, has been obtained from an aqueous solution and characterized. The partial replacement of Br by I resulted in the formation of a thermally stable (<155 °C) black compound (C15 H14 N4 )BiBrI4 ·H2 O with an optical band gap of 1.70 eV, which can be proposed as a promising light-harvesting material for dye-sensitized solid-state solar cells. Further replacement of Br by I results in the formation of red-orange colored (C15 H14 N4 )BiI5 with a band gap of 2.10 eV.